Doctor, do you have a moment? National Hand Hygiene Initiative compliance in Australian hospitals. Issue 9 (19th May 2014) - Azim, Syed; McLaws, Mary‐Louise
Abstract: Objectives: To examine hand hygiene compliance rates for medical and nursing staff, compliance with hand hygiene before touching a patient (Moment 1 of the Five moments for hand hygiene), and the effect of differential sampling of staff on the average national rate. Also, to establish whether hand hygiene rates impact Staphylococcus aureus bloodstream infections (SABSI). Design and setting: Analysis of data from three different cross‐sectional datasets — Hand Hygiene Australia data for 246 665 hand hygiene opportunities during the first quarter (1 January to 31 March) of 2013 from 82 public hospitals representing eight Australian states and territories, and hand hygiene rates and SABSI rates from the MyHospitals website reported for 1 July 2011 to 30 June 2012. Main outcome measures: Compliance by medical and nursing staff for each hospital size (> 400 beds, 301–400 beds, 201–300 beds, and 101–200 beds); the proportion of hospitals with hand hygiene compliance rates for before touching a patient at or above, or below the national threshold of 70%; the impact of hand hygiene on SABSI. Results: Medical staff consistently performed below the national threshold for hand hygiene compliance regardless of hospital size. Nurses' compliance was consistently above the threshold, and this inflated the total average national rate. A third of the patient interaction hand hygiene opportunities recorded involved before touching a patient, for which compliance was below the national threshold in 68% of hospitals. Hand hygiene has little impact on the rate of SABSI (incidence rate ratio, 0.97; P < 0.01). Conclusions: Posting a national unadjusted average hand hygiene compliance rate on a public website conceals the fact that most hospitals and medical staff are performing below the national hand hygiene compliance threshold. Given the poor compliance after 4 years of auditing to capture non‐compliance, we must shift our focus to providing medical staff with immediate feedback and move to improving a single hand hygiene indication at a time, starting with before touching a patient .